Nucleoside diphosphate kinase B regulates angiogenic responses in the endothelium via caveolae formation and c-Src-mediated caveolin-1 phosphorylation - Gross, Shalini; Feng, Yuxi; Wieland, Thomas (Journal of cerebral blood flow & metabolism, 2017)
Nucleoside diphosphate kinase B (NDPK-B) is an enzyme required for nucleoside triphosphate homeostasis, which has been shown to interact with caveolin-1 (Cav-1). In endothelial cells (ECs), NDPK-B contributes to the regulation of angiogenesis and adherens junction (AJ) integrity. We therefore investigated whether an interaction of NDPK-B with Cav-1 in ECs is required for this regulation and the involvement of VEGF signaling herein. We report that simultaneous depletion of NDPK-B/Cav-1 in HUVECs synergistically impaired sprouting angiogenesis. NDPK-B depletion alone impaired caveolae formation, VEGF-induced phosphorylation of c-Src/Cav-1 but not of ERK1/2/AKT/eNOS. In vivo, Cav-1-/- mice showed impaired retinal vascularization at postnatal-day five, whereas NDPK-B-/- mice did not. Primary mouse brain ECs (MBMECs) from NDPK-B-/- mice showed no change in caveolae content and transendothelial-electrical resistance upon VEGF stimulation. Interestingly, NDPK-B-/- MBMECs displayed an accumulation of intracellular vesicles and increased Cav-1 levels. Dextran tracer analysis showed increased vascular permeability in the brain of NDPK-B-/- mice compared to wild type. In conclusion, our data indicate that NDPK-B is required for the correct localization of Cav-1 at the plasma membrane and the formation of caveolae. The genetic ablation of NDPK-B could partially be compensated by an increased Cav-1 content, which restored caveolae formation and some endothelial functions.